Infection Control Measures Concerning Knowledge and Behavior among Bangladeshi Dental Professionals - Asma Begum; Bilkis Banu; Nasrin Akter; Sujana Chowdhury; Mohammad Shardar; Nusrat Nobi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Maintenance of universal infection protocol in all dental care processes in the dental office before, during, and immediately after dental care is of utmost importance. Very few studies were found to identify the bio-security standards for dental care. This study aimed to determine the knowledge and behavior of Bangladeshi dental professionals on the infection control system during clinical case management.Material and methods: This descriptive cross-sectional study was conducted among 110 dental professionals in the Khulna district, Bangladesh. Semi-structured data were collected in this study through the face-to-face interview method.  Univariate multivariate techniques followed by regression modeling have been used for analysis.Results: About 67% of dental surgeons knew about infection prevention measures well, whereas only 33% had poor knowledge. However, instead of having good knowledge of infection control measures, 33% of dental surgeons were found to have poor behavior in their dental setting, and the rest, 34%, followed all the preventive measures to control infection. Binary regression analysis of this study revealed significant predictors associated with poor knowledge and behavior on infection control measures.Conclusions: This study revealed a depressive scenario regarding knowledge and behavior on infection control measures among dental professionals. A large-scale study is required to generalize the information and to improve the situation. Moreover, this study will provide a concrete base for further study and will significantly assist the policymakers of the pertinent arena.